Some antecedents and outcomes of passionate desire for fashion clothes and accessories - Loureiro, S. M. C.; I. Costa (Conference book proceedings of 9th Euromed conference of the Euromed academy of business research- innovation, entrepreneurship and Digital Ecosystems, 2016)
Fashion trends and consumer-fashion brand relationships have been subject of study for both researchers and practitioners. Yet, as far as we know, there is a lack of analysis of the process behind the creation of a fashion trend, in previous studies. Therefore the main goal of this research was to start to understand the process behind the creation of a fashion passion for clothes and accessories, particularly to understand in what extend do narcissism and social values influence passionate desire and then, the way passionate desire influences positive word-of-mouth and affective commitment. Findings reveal that Social values have a positive and significant direct effect on Passionate desire. Yet, the strength of the relationship between Narcissism and Passionate desire is weak. The strength of the relationship between Passionate desire and word-of-mouth is weaker than the relationship between Passionate desire and Affective commitment. The current study also provides managerial implications and suggestions for further research.